Risk charakterization of microbiological hazards in food : guidelines (WHO, 2009)
Risk characterization is one of the four steps of microbiological risk assessment, which include hazard identification, exposure assessment, hazard characterization and risk characterization. Risk characterization is defined as an estimation of the probability of occurrence and severity of known or potential adverse health effects in a population based on hazard identification, hazard characterization and exposure assessment. It is in the risk characterization step that the results of the risk assessment are presented. These results are provided in the form of risk estimates and risk descriptions that present answers to the questions risk managers pose to risk assessors. These answers, in turn provide the best available science-based evidence to be used by risk managers to assist them in managing food safety.This volume presents guidelines for risk characterization of microbiological hazards in foods. These guidelines provide descriptive guidance on how to conduct risk characterizations in various contexts, and utilizing a variety of tools and techniques. They have been developed in recognition of the fact that reliable estimation of risk is critical to the overall risk assessment.This volume and others in the Microbiological Risk Assessment Series contain information that is useful to both risk assessors and risk managers, including international scientific committees, the Codex Alimentarius Commission, governments and food regulatory agencies, scientists, food producers and industries and other people or institutions with an interest in the area of microbiological hazards in foods, their impact on human health and food trade and their control.
Microbiological risk assessment series, ISSN 1726-5274 No. 17
Keywords: hodnocení rizik; bakteriologie; hygiena; zemědělství a potravinářství; Food Contamination; mikrobiologie, lékařská mikrobiologie; kontaminace potravin; Risk Assessment; Bacteriology